Impact of the COVID-19 Pandemic on Stress, Sleep, and Oral Health in University Students - Cerqueira, Thaissa Reis do Carmo; Batista, Sayene Garcia; de Mello, Elson Braga; DosSantos, Marcos Fabio; Tuñas, Inger Teixeira de Campos (Frontiers in Pain Research, 2021)
Background: The COVID-19 pandemic, a disease caused by Sars-CoV-2, has become a worldwide stressor, especially as it represents a new viral infection, which spreads quickly and easily, without prior knowledge about vaccination, and absence, to this moment, of a medication that is totally effective against the disease. Objective: The aim of this observational study was to provide a general evaluation, through a questionnaire applied to students in the health field of the Federal University of Rio de Janeiro, on the psychological impacts and behavioral changes generated by the COVID-19 pandemic on oral health, especially the triggering or exacerbation of bruxism and temporomandibular disorders (TMD). Methods: In order to verify the impacts of the pandemic on the health of UFRJ healthcare students, a non-randomized survey was performed with 370 students. Results: It was found that 72% of the students had their sleep routine altered, 65% had greater difficulty in keeping their spirits up, there was a statistically significant increase in emotional stress, headaches, and daytime teeth clenching. Conclusion: It was possible to conclude that the outbreak of COVID-19 resulted in psychological, physiological and behavioral impacts on students.